Search for near room-temperature superconductivity in B-doped Q-carbon. Issue 4 (3rd April 2019) - Narayan, J.; Sachan, R.; Bhaumik, A.
ABSTRACT: We present 1D, 2D and 3D structures of boron-doped Q-carbon with a higher superconducting transition temperature than the current value of 55 K in 25 at% B-doped amorphous Q-carbon. The higher transition temperature is predicted for 1D and 2D crystalline structures with increasing density of states near the Fermi level through dopant trapping in substitutional sites. We have synthesized 50at% B-doped Q-carbon where diamond tetrahedra are arranged randomly and packed with over 80% efficiency to generate an amorphous structure. Detailed EELS measurements show higher density of states near the Fermi level above 90 K and preliminary transport data show signature of T c above 100 K. GRAPHICAL ABSTRACT: IMPACT STATEMENT: Novel 1D, 2D and 3D structures of boron-doped Q-carbon with higher Tc than current BCS record of 55K by increasing B-concentration and the density of states near the Fermi level.